Loss of Knee Flexion and Femoral Rollback of the Medial-Pivot and Posterior-Stabilized Total Knee Arthroplasty During Early-Stance of Walking in Chinese Patients - Tan, Jiaqi; Zou, Diyang; Zhang, Xianlong; Zheng, Nan; Pan, Yuqi; Ling, Zhi; Tsai, Tsung-Yuan; Chen, Yunsu (Frontiers in Bioengineering and Biotechnology, 2021)
Background: The medial-pivot (MP) prosthesis was developed to produce more physiological postoperative knee kinematics and better patient satisfaction than traditional prostheses, but outcomes are inconsistent in different studies of Caucasian patients. This study aimed to investigate the postoperative patient satisfaction and in-vivo knee kinematics of the MP and posterior-stabilized (PS) prosthesis during gait activity in Chinese patients. Methods: A retrospective analysis of 12 patients were received for this study in each MP group and PS group. Patient-reported satisfaction level and Forgotten Joint Score (FJS) were evaluated with questionnaires. A dual fluoroscopic imaging system was used to investigate in-vivo knee kinematics of MP and PS TKA during treadmill walking at a speed of 0.4m/s. Results: Comparable promising patient satisfaction and overall FJS (MP 60.7±15.35 vs. PS 51.3±17.62, p= 0.174) were found between the MP and PS groups. Peak flexion appeared at around 70% of gait cycle with values of 52.4°±7.4° for MP and 50.1°±3.6° for PS groups (no difference). Both groups maintained a stable position at the stance phase, and began to translated anteriorly at toe-off with an amount of 4.5±2.3 mm in the MP and 6.6±2.7 mm in the PS (p= 0.08) group until late swing. The range of this external rotation motion was 5.9°±4.8° and 6.2°±4.1° (p= 0.79) for the MP and PS, respectively. Conclusion: A similar knee kinematics pattern characterized by a loss of early-stance knee flexion and femoral rollback during walking was observed in the MP and PS TKAs. Our study confirmed similar effectiveness of MP TKA compared to PS TKA in Chinese patients, while the change of knee kinematics of both implants during slow walking should be noted.